Dampak Kejadian La NiÃ±a Terhadap Curah Hujan Di Kabupaten Jembrana - Baiq Helmi Susrinda; Wahyu Widodo Putranto (Kappa Journal, 2019)
Rainfall variability in Indonesia could be affected by global phenomenon like La NiÃ±a by looking at the intensity value of Southern Oscillation Index (SOI) and anomaly value of SPL. The amount of these effect varies from one place to another. Jembrana Regency is one of the Regency of Bali Province. Jembrana Regency is located at 8°09'30" - 8°28'02" SL and 114°25'53" - 114°56'38" EL. The west and south border of Jembrana Regency are the sea which are Bali Strait and Indian Ocean, whereas the its east and north border are Buleleng Regency and Tabanan Regency. Rainfall pattern of Jembrana Regency has a peak of the rainy season between December - February and a valley of the dry season between June - August. From monthly rainfall data taken from the rain post of Poh Santen, Rambutsiwi, Palasari and Negara, descriptive statistical method was used to calculate the average monthly rainfall during the period of 30 years during period of 1981-2010. La NiÃ±a of 2010 affected the amounts of rainfall that is greater than its average in Jembrana Regency Bali. La NiÃ±a of 2010 affected the amounts of rainfall that is greater than La NiÃ±a period of the previous years.